New material of Katepensaurus goicoecheai (Sauropoda: Diplodocoidea) and its significance for the morphology and evolution of Rebbachisauridae - Ibiricu, Lucio Manuel (2015)
Cretaceous outcrops in southern South America preserve a rich and evolutionarily important record of sauropod dinosaurs. Among Sauropoda, South American titanosaurs have garnered particular interest due to their abundance and taxonomic diversity. Nevertheless, the fossil record of rebbachisaurids has also improved significantly in recent years, and consequently so has knowledge of the group. However, many aspects of the anatomy and phylogenetic relationships of Rebbachisauridae remain unresolved, due in large part to the fragmentary nature of many members of the clade. Within this context, we describe new fossils of Katepensaurus goicoecheai Ibiricu, Casal, Martínez, Lamanna, Luna, and Salgado, a recently-named rebbachisaurid from the Upper Cretaceous (Cenomanian/Turonian) Bajo Barreal Formation of central Patagonia (Argentina). Based on these additional materials, we propose two new autapomorphies of this taxon: (1) ventral portion of posterior articular surface of anterior dorsal vertebral centrum wider than dorsal portion, conferring a ‘teardrop-shaped’ contour; and (2) ovoid fossa on dorsal aspect of anterior to middle dorsal vertebral transverse processes. These features enhance our understanding of morphological diversity within Rebbachisauridae and augment the diagnosis of Katepensaurus. Furthermore, phylogenetic analysis confirms the assignment of this taxon to the rebbachisaurid subclade Limaysaurinae. Katepensaurus is the southernmost record of a rebbachisaurid that is identifiable to the generic level.